Nilai-nilai kepahlawanan dalam teks Takna’ Lawe’ daripada komuniti Kayan di mendalam: Kajian semiotik / Albert Rufinus - Albert, Rufinus (2017)
Takna` Lawe` is one of the literary genres in a lyric prose form with 6,537 stanzas. It can be performed with a rhythmic movement by men and is usually accompanied with dances by the women. The story is believed to tell about Lawe`, a god or soul, and his superhuman power, heroic fights in the world of gods and goddesses. In accordance with the Kayan community traditions, Takna` Lawe` tells in part about the history of Kayan community in poetic forms who lived in their world on earth with their indigenous customs or traditions; how the community lived and communicated well with the world of the souls. The research on this thesis was focused on the analysis of the stanzas of the four Takna` Lawe` books. First of all, the four central ideas or themes were set up representing the respective four books. Secondly, in view of the big stanzas to analyse, a systematic cluster (random) sampling was taken when drawing the samples of the total stanzas (6,537 stanzas) of which then twenty-five episodes were categorised. These twenty-five episodes consisted of 200 stanzas and analysed using Peircean Semiotics Theory. Based on the qualitative method, the research problem questions were (1) How to categorise heroism in Takna` Lawe` texts with reference to sign categories and is based on Peircean Semiotics Theory? (2) How to elaborate for the sign meanings of Lawe` heroism which is based on Peircean Semiotics Theory? (3) How to examine the messages and values of Lawe` heorism which are based on Lawe` Heroism Profile, i.e., Human Hero, Divine Hero, and Warrior Hero? The research objectives were (1) to categorise heroism in Takna` Lawe` texts with reference to sign categories and is based on Peircean Semiotics Theory; (2) to elaborate for the sign meanings of Lawe` heroism which is based on Peircean Semiotics Theory; (3) to examine the messages and values of Lawe` heorism which are based on Lawe` Heroism Profile, i.e., Human Hero, Divine Hero, and Warrior Hero. The analyses of the twenty-five episodes then showed the concepts of Lawe`s heroism for heroic messages and heroic values. The findings, based on Peircean Semiotics Theory of Takna` Lawe` texts, show that Lawe` is qualified and indexed as an iconic hero of bravery, smartness, superhuman, well in attitude, full of responsibility, and full of love. Moreover, based on Lawe` Heroism Profile, he is characterised as (1) the Human Hero in values of Smartness, Cooperation, Sacrifice, Loving and Caring, and Beauty; (2) the Divine Hero in values of Strength and Superhuman Power; (3) the Warrior Hero in values of Braveness and Patriotism. In both qualitative and quantitative frequencies of interpretation, the findings of values of Lawe`s heroism are profiled as 24 in smartness, 122 in cooperation, 17 in sacrifice, 47 in caring and beauty, 40 in loving, 59 in supernatural strength, 55 in superhuman power, 74 in braveness, and 73 in patriotism. This is qualified as high and super of Lawe`s great adventure, wars, and especially his love and success for his wife, Karigit, his beautiful ladies, and his community.